A’uwẽ höimanadzé : práticas de resistência na produção audiovisual Xavante - Costa, Gilson Moraes da (2019)
Popularization and access to new communicability mechanisms added to the pressure of sectors of civil society by democratic models of communication enabled a growing number of individuals and collectives to produce exchange and disseminate content making use of different technologies. In this scenario, audiovisual productions that, until the mid-1970s, were mostly carried out by large agents and institutions (state and private broadcasters, film studios and large producers) began to gain space in sectors alternative and popular. In a context of articulation of Indigenous Peoples in Brazil, the appropriation of the media, especially those of audiovisual production, establishes expressive channels for self-determination and selfrepresentation affirming itself as a relevant resource in the landscape of political disputes and objecting to a regime of visibility imposed by a colonialist logic. In this research, we seek to evidence how Xavante groups have adopted different resistance practices in different historical periods, signaling an analytical panorama from the process of contact with the surrounding society to contemporary times. We argue that, if at first, isolation and embattled posture were strategies of ethnicity as a form of direct struggle against the expropriation of their territories, after contact, occurred around 1947, the articulations in the sphere of culture are configured as important subterfuge in the continuous process of resistance and struggle for the acquisition and guarantee of rights. Starting from an interdisciplinary analytical proposal, as well as the ethnographic experiences experienced in the research, we demonstrated that audiovisual, produced by people and collectives xavante in the context of different partnerships, has occupied a relevant role in the field of "identity politics" (GRAHAM, 2005) of ethnicity. The corpus of this research consists, in part, by documentaries produced by filmmakers from the indigenous lands São Marcos, Sangradouro and Pimentel Barbosa, all inserted in the state of Mato Grosso. We identify in these initiatives a cinema that overflows the very constitution of the image, whose symbolic, cultural and political representation are beyond the limits of the film framework. Considering the analyses undertaken here, it is possible to consider that the look built with the camera by the xavante filmmakers assumes uniqueness capable of producing narratives that escape the standardization of the modern documentary truth regime, providing vigorous means for cultural affirmation, community sociability, for the valorization of ethnic identity and as an instrument that expands the possibilities of the different struggles and challenges faced by Xavante groups in the relationship with society Surrounding.